Olefination with Sulfonyl Halides and Esters: E‐Selective Synthesis of Alkenes from Semistabilized Carbanion Precursors. Issue 15 (19th April 2018) - Górski, Bartosz; Basiak, Dariusz; Talko, Alicja; Basak, Tymoteusz; Mazurek, Tomasz; Barbasiewicz, Michał
Abstract : Carbanions of sulfonyl halides and activated sulfonates add to carbonyl compounds, and so‐formed aldol‐type adducts spontaneously fragment into olefins. This transformation mimics the one‐pot Julia olefination with (hetero)aryl sulfones, but the mechanism of fragmentation involves a four‐membered intermediate, typical for reactivity of phosphorus reagents. Moreover, in contrast to the reactions of sulfones, sulfonates of fluorinated alcohols (TFE and HFI) produce byproducts that are easily removed during workup. In our report, we focus on reactions of unstabilized and semistabilized carbanion precursors: alkylsulfonates, and allyl‐ and benzylsulfonates, respectively. In particular for semistabilized systems, olefins were synthesized as predominant E isomers in good yields. The presented studies reveal that optimal reaction conditions, including the type of base and alcohol groups of the sulfonates, are different depending on stabilization of the carbanion precursors and structure of the carbonyl substrates. The practical synthetic guide is supplemented with a discussion of the mechanism, based on reactivity studies of intermediates and identification of side‐products. Abstract : Sulfur‐based olefination with Horner–Wadsworth–Emmons‐type mechanism is systematically studied. Nonstabilized and semistabilized carbanion precursors react with carbonyl compounds giving good yields of olefins, and for the latter reagents E isomers of alkenes predominate.